Joint optimization algorithm for enhanced inter-cell interference coordination in heterogeneous networks - Lai-wei JIANG; Xuan-li WU; Nai-tong ZHANG (Tongxin xuebao)
The total system throughput was improved by means of enhanced inter-cell interference coordination (eICIC)in heterogeneous networks(HetNets)in LTE-Advanced system. Through analyzing the existing system interference, mathematical model was established and a joint optimization algorithm for eICIC was raised based on the reduced power almost blank subframe. By using this optimized method, the relationship between the total system throughput and the re-duced power almost blank subframe was studied, so as to realize the maximized total system throughput and solve the problems of the amount of radio resources that macro cells should offer to pico cells and UE assignments. Simulation re-sults show that, compared with the comparative method, the proposed method has 19.8% improvement in the total system throughput and the optimality gap is 97.4%. Conclusions can be drawn that the proposed method is suitable for the scene where the total system throughput requirement is relat vely high while the performance of the edge user requirement is relatively low.